Cuando el derecho procesal y el arbitraje se encuentran - Pulido Del Pino, Natalí Juliana (2023)
This article is a reflection that, using doctrine and jurisprudence, aims to evaluate what happens with the determination of jurisdiction when we are faced with pathological clauses. Although, in principle, we should refer to arbitration, in some exceptional cases the disputes will end up being settled by the Judiciary. For these purposes, we start from the concept of the arbitra tion clause; then, we will deal with the exception of the arbitration agreement, where the types of pathologies that can be found are developed; and we will analyze what has happened, in practice, in the Peruvian national courts, to finally determine who will be the competent authority in each specific case.